Actividades recreativas fluviales como mecanismo de reactivación turística del río Babahoyo - Machado Bajaña, Maikeel Marilin (2020)
Babahoyo known in colonial times as a winery, is the cantonal head belonging to of the Los Ríos province, it´s located in the center of the coastal region. It has a very important water resource called the Babahoyo River divided by two rivers; San Pablo and Catarama, place where the following case study will be analyzed, with the aim of proposing river recreational activities to analyze the tourist reactivation of the Babahoyo River. River recreational activities are groups of activities that take place in freshwater spaces, offering the opportunity for fun and enjoyment to each individual. Regarding the tourist reactivation, it refers to developing strategies in those resources or tourist places that have limited importance and that can be taken to reestablish tourism within the city. This analysis is aimed at public and private companies that are those that guarantee tourism development, through the strategies or projects proposed by professionals, so that they benefit, the population in general is also favored, allowing human development through active practice. In addition, these actions increase the economic resource and improve the quality of life of its inhabitants. One of the problems detected is that the Babahoyo River is not used for tourism, due to the little support that there is in public and private companies, consequently the inhabitants use the river only for daily activities. On the other hand, the technique applied for the collection of information was the survey, being applied to 100 people, resulting in the agreement of the population to implement recreational river activities to reactivate tourism in the city.